Application of the Continuous Stamping Technology in the Manufacture of Tines Tooth Chain - Fan Lei; Wang Lili; Sun Bin (Jixie chuandong)
The shape of parts and processing technology is analyzed in detail,the stamping layout feasibility scheme is formed,by using the process comparison method,the tines tooth chain plate stamping forming process in the improvement of production efficiency,energy consumption,environmental and other parties are introduced. According to the size of the mass production,two direction is improved from the following: adopts semi shearing blanking process,to further enhance the chain plate flatness; When the sharp teeth quality requirements is not high,small batch manufacturing process,using composite stamping processing.